MISPERSEPSI PEMIDANAAN PERTANGGUNGJAWABAN KORPORASI ATAS PENGGUNAAN FAKTUR PAJAK FIKTIF OLEH DIREKSI - Ryan Apriyandi (Jurnal USM Law Review, 2022)
This study aims to analyze corporate responsibility for the crime of using fictitious tax invoices by directors and how the judge's basic considerations in the decision of the Tanjung Karang District Court No. 343/Pid.Sus/2021/PN.Tjk. This research is motivated by the rise of taxpayers who are reluctant to pay taxes obediently to the state. Corporations take advantage of this loophole by issuing fictitious tax invoices to reduce funds that should be deposited into the state treasury and later the corporation will ask for restitution from the state. The research method used is a normative juridical method with a statutory approach, a conceptual approach and a case approach. The novelty in this research is to complement the studies conducted in previous studies which only criminalize individual management or corporate directors in criminal acts in the field of taxation, without considering corporate responsibility as legal subjects who can be held criminally responsible and the need for optimization by the DGT in the development of e-commerce applications. Nofa, both in terms of administration and technicality, so that dynamic applications can be realized and can reduce the use of fictitious tax invoices in Indonesia. The results of the study show that with the prevalence of cases of issuing fictitious tax invoices by directors, corporations must be fully responsible for criminal acts committed because they are very detrimental to state finances